Memorendum on the german iron trade in 1900 and 1901 : presented to both Houses of Parliament by command of His Majesty, April, 1902 - Grande-Bretagne. Foreign Office
3 tabl. dépl. h. t. Antériorité : "Reference to previous report, annual series n° 553"